Literature Review Comparing Laparoscopic and Percutaneous Endoscopic Gastrostomies in a Pediatric Population - Madelen Lantz; Helena Hultin Larsson; Einar Arnbjörnsson (International Journal of Pediatrics)
Objective. This study compares laparoscopic and percutaneous endoscopic gastrostomy (PEG) in a paediatric population to test the hypothesis that there is a difference in the frequency of serious gastrointestinal complications between the two methods. Methods. All reports published between 1995 and 2009 on laparoscopic gastrostomy and PEG in children was included. Prospective and retrospective trials, comparing the two methods or dealing with one of them only were included. Endpoints were accidentally performed gastrointestinal fistula causing an emergency re-operation. The frequency of inadvertent gastroenteric fistulas using the two different techniques was calculated. Results. 822 publications were found when using the search terms: gastrostomy, gastrointestinal complications, and all child: 0–18 years. From these, 54 studies were extracted for this investigation. These studies reported a total of 4331 children undergoing gastrostomy operation, 1027 by using the laparoscopic technique and 3304 using the PEG technique. The number of serious gastrointestinal fistulas to colon or small bowel was 0% and .27%, respectively, P<.05. Conclusions. The results suggest that by performing laparoscopic gastrostomy in children it is possible to avoid the serious intestinal fistula complications caused by a blind puncture through the abdominal cavity when performing the PEG.